UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 70% KLIKA TURI (Sesbania grandiflora L.) TERHADAP Staphyloccous epidermidis DAN Propionibacterium acnes - Andi Dian Astriani (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
AcneÂ is a skin disease that occurs due to bacterial infection, usually on the skin surface of the face, neck, chest, and back. The Turi plant is one plant with medicinal properties that can be used as an antibacterial. This study aims to determine the antibacterial activity of 70% ethanol extract of klika turi against Staphylococcus epidermidis and Propionibacterium acnes. Klika turi was extracted by reflux method using 70% ethanol solvent. They were testing the antibacterial activity of 70% ethanol extract against Staphylococcus epidermidis and Propionibacterium acnes using liquid dilution and agar diffusion methods. The results showed that the MIC values were 2.5% against Staphylococcus epidermidis and 5% against Propionibacterium acnes. Activity test with the diffusion method to obtain the diameter of the inhibition zone against Staphylococcus epidermidis at an extract concentration of 2.5%; 5%; 10%; and 20%, which is 7.35 mm; 8.67mm; 11.08 mm and 11.55 mm, while for Propionibacterium acnes at an extract concentration of 5%; 10%; and 20% obtained the diameter of the inhibition zone which is 8.77; 11.32mm; and 12.00mm. The results can be concluded that the 70% ethanol extract of klika Turi has effective antibacterial activity at a concentration of 10% against Staphylococcus epidermidis and Propionibacterium acnes.).